PERKEMBANGAN JIWA BERAGAMA PADA ANAK DI MI NW TANAK MIRA DESA WANASABA LAUK - Hully Hully; Irwan Irwan (Universitas Pahlawan Tuanku Tambusai, 2022)
This paper aims to find out the development of the religious spirit in children at MI NW tanak Mira, Wanasaba Lauk Village. This is very important because the development of the religious spirit in children is not the same when entering adolescence and adulthood. The more religious values ​​are obtained, the attitudes, behavior, patterns of thinking and actions and the way children face life are increasingly in line with or in accordance with religious teachings. The research method used is qualitative with data collection techniques using observation, interviews and documentation. Data analysis was carried out logically, systematically which included three stages, namely data reduction, data display, conclusion drawing. From the results of the studies conducted, it is shown that the development of the religious spirit in children is characterized by an attitude of imitation, then starting from the level of fairy tales, reality and individualism. The efforts made to instill religious education in children at Madrasah Ibtidaiyah (MI) NW Tanak Mira, Wanasaba Lauk Village can be done by instilling a religious sense in children, guiding and directing the development of children's souls through Islamic religious education and instilling good ethics in children. based on religious norms. So, it can be concluded that the development of the religious spirit in children is not the same or different from adolescence along with the level of physical and psychological development. Keywords: Development, Religious Spirit, Children